Comparative clinical outcomes of polymyxin-based versus non-polymyxin regimens as definitive therapy in Carbapenem-resistant Klebsiella pneumoniae bacteraemia - Divya Bhat; Asha K. Rajan; Vandana Kalwaje Eshwara; Muralidhar Varma; Shashikiran Umakanth; Girish Thunga; Vishal Shanbhag (PLoS ONE, 2026)
Background Carbapenem-resistant Klebsiella pneumoniae (CRKP) bacteraemia poses a major therapeutic challenge due to limited effective therapeutic options and high mortality. Although polymyxins remain widely used, emerging evidence suggests that non-polymyxin regimens may offer improved efficacy and safety. This study compared clinical and microbiological outcomes between polymyxin-based therapy (PBT) and non-polymyxin regimens (NPR) in patients with CRKP bloodstream infections (BSI). Methods In this multicentric, retrospective observational study, adult patients (≥18 years) with confirmed CRKP bacteraemia admitted between January 2019 and December 2023 were included. Patients were categorised based on definitive therapy as PBT or NPR. Baseline characteristics, disease severity, and outcomes were compared using appropriate statistical tests. Predictors of in-hospital mortality were identified by multivariable Cox regression, validated by bootstrap resampling, and assessed through landmark sensitivity analysis excluding early deaths (<48 hours). Kaplan-Meier survival analyses were performed for mortality and microbiological clearance. Results Of 1,009 patients with K. pneumoniae bacteraemia, 244 patients with CRKP met inclusion criteria (PBT, n = 143; NPR, n = 101). Baseline demographics were similar, but PBT recipients had higher SOFA (4[0–12] vs.3[0–12]; p < 0.001) and CCI scores (4[0–8] vs.3[0–10]; p = 0.025). Clinical cure was achieved more often with NPR (58.4%vs.15.4%; p = 0.02), while in-hospital mortality (38.6%vs.68.5%; p < 0.001) and acute kidney injury (28.7%vs.55.9%; p = 0.008) were significantly higher in the PBT group. Microbiological clearance and time to clearance were comparable. Independent predictors of mortality included treatment with polymyxins (aHR:1.595;95%CI:1.392–1.903;p = 0.015), SOFA score>6 (aHR:1.514;95%CI:1.285–1.928;p = 0.027), history of chronic liver disease (aHR:2.31;95%CI:1.884–3.642;p = 0.02), post-therapy dialysis (aHR:3.11;95%CI:1.008–4.59;p = 0.048), and requirement of ICU admission after definitive therapy (aHR:1.474;95%CI:1.252–1.891;p = 0.02). Survival analysis confirmed superior outcomes for NPR (log-rank p < 0.001). Conclusion NPR was associated with significantly higher clinical cure, lower nephrotoxicity, and reduced mortality compared with PBT regimens. These findings suggest that non-polymyxin regimens may be associated with improved clinical outcomes and lower nephrotoxicity compared with polymyxin-based therapy in patients with CRKP bacteraemia. Prospective studies were warranted to confirm these observations.